Effect of Phenolic Substances and Hydrogen Peroxide on Antioxidant Activity of Some Strains of Basidiomycetes - Fedotov, Oleh; Bisko, Nina (Innovative Biosystems and Bioengineering, 2018)
Background. Development of the method of regulation and biotechnology of antioxidant action specimen production of mycological origin. Objective. The aim of the paper is to study the effect of phenolic type chemical substances and hydrogen peroxide on the antioxidant activity of some basidium fungi strains in cultivation in the laboratory. Methods. Cultivation of basidium fungi strains by periodic superficial method on glucose-peptone medium in flasks. Results. The influence of sodium lignosulfonate, tannin, gallic acid and hydrogen peroxide in 0,1 % concentration at 24 and 48 hours of exposure on the antioxidant activity of some basidium fungi strains was studied. Conclusions. The most productive basidium fungi strains were found on the level of antioxidant mycelial activity: P-er Pleurotus eryngii > > Р-сіtr Pleurotus citrinopileatus > P-035 Pleurotus ostreatus > Fh-08 Fistulina hepatica > 960 Agrocybe cylindracea. The highest values of the total antioxidant activity of the culture fluid got the following strains: Р-081 > Р-082 > Р-087 Pleurotus ostreatus > Р-сіtr Pleurotus citrinopileatus. Antioxidant-producing strains can be used as biological agents in biotechnology for functional products or prophylactic drugs. The highest degree of AOA mycelium induction was observed with addition of: sodium lignosulfonate – by 164 %, after 48 hours of exposure, of the strain 960 Agrocybe cylindracea; tannin – by 147 %, after 48 hours of exposure, of the strain Fh-08 Fistulina hepatica; gallic acid – by 121 %, after 48 hours of exposure, of the strain 960 Agrocybe cylindracea; hydrogen peroxide – by 114 %, after 48 hours of exposure, of the strain Fh-08 Fistulina hepatica.